2003
DOI: 10.1046/j.1397-3142.2003.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after renal transplantation in children: Results of follow‐up by nephrologists in a primary referral center

Abstract: Pediatric patients who receive a kidney transplant require extended follow-up to monitor graft function and for management of complications. Because of convenience, most patients are sent back to the nephrologists who referred them for transplantation (the primary nephrologist) for long-term care. As a consequence, many pediatric nephrologists who provide this extended care are not associated with a transplant center. It is not known if this arrangement yields satisfactory outcomes for children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The follow-up of all patients was performed in our institution. The study comparing pediatric patients followed in the same institution where the transplant was performed to patients accompanied by their original nephrologists did not show any difference in the evolution of both groups (12).…”
Section: Commentsmentioning
confidence: 84%
“…The follow-up of all patients was performed in our institution. The study comparing pediatric patients followed in the same institution where the transplant was performed to patients accompanied by their original nephrologists did not show any difference in the evolution of both groups (12).…”
Section: Commentsmentioning
confidence: 84%
“…This model ensures that the patient is monitored by the transplant team and complications are quickly identified and treated. 14 In 2003, Adedoyin et al 14 suggested that pediatric patients could be safely and effectively managed at their referring center after transplant and that alternating visits creates confusion for their families. In our experience, it is the referring nephrologists' goal to manage their nephrology patients after transplant, with the transplant center available for both ongoing consultation and inpatient care should the patient require therapies not available at the referring hospital.…”
Section: Communication With Outside Providersmentioning
confidence: 99%